Effect of Taxpayer Awareness, Tax Knowledge, and Tax Socialization on Taxpayer Compliance in Paying Land and Building Tax - Windi Pransiska; Irine Ika Wardhani (Universitas Medan Area, 2022)
Land and Building Tax is an important income for each region, therefore each local government has its own way to optimize income from the land and building tax sector. This study aims to examine and analyze the effect of taxplayer awareness, tax knowledge, and tax socialization on taxpayer compliance in paying land and building taxes in Cinta Rakyat village, Percut Sei Tuan District. This study uses primary data where data is collected directly from the results of questionnaires. This research was conducted on land and building taxpayers in Cinta Rayat Village starting in March with a population of 2,125 taxpayers in 2022 with a sample of 96 respondents. The results of the analysis show that taxpayer awareness and knowledge of taxation partially affect taxpayer compliance. While the socialization of taxation partially has no effect on taxpayer compliance. The results of the analysis prove that taxpayer awareness, tax knowledge, and tax socialization partially affect taxpayer compliance.